Growth and Production of Pakchoy Under Various Type of Organic Fertilizer - R. Rahmawati (Universitas Sembilanbelas November Kolaka, 2020)
This study was conducted in Wiringpalenna village, Tempe sub-district of Wajo district, with the aim to determine the effect of the type of organic matter on the growth and production of pakchoy plants. The study was arranged based on a Randomized Block Design with five treatments namely: without organic matter, chicken manure, Blotong (Filter press mud), bokashi common water hyacinth, bokashi rice straw. The results showed that from variables tested; plant height, the number of leaves, the width of leaves, fresh weight of plants, fresh weight of plants per plot, and fresh weight per hectare, treatment with bokashi common water hyacinth obtained the best result